PENGARUH DISIPLIN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PEMERINTAHAN KECAMATAN SIBOLGA SAMBAS - Bella Saputri Tanjung; Mansur Tanjung; Nurainun Hasibuan (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2025)
Writing this thesis aims to determine the effect of work discipline and work experience on employee performance at the Sibolga Sambas government office. The problem encountered in this study is that there are still employees who are not disciplined and lack experience in their work.The formulation of the problem in this research is Is There Any Influence Of Work Discipline And Work Experience On Employee Performance At The Sibolga Sambas Government Office? While the purpose of this study was to find out whether there is an influence of work discipline and work experience on employee performance at the Sibolga Sambas Government Office? The proposed hypothesis is that there is an effect of work discipline and work experience on employee performance at the Sibolga Sambas government office. The population in this study were PNS and THL employees at the Sibolga Sambas District Government Office totaling 70 people. The data collection technique is done by distributing questionnaires. The data analysis technique used is quantitative analysis.The results of the study show that the relationship between work discipline and work experience on employee performance is a strong category, where the calculation of the normality of the data is 1.65. While the coefficient of determination obtained 26.3%. T-test > t table 3,810 > 2,02108 at a significance level of 0.0000 < 0.05. The equation of the simple linear regression model is Y = 36,112 + -0,512.It can be concluded that, Ha is accepted. For this reason, it is recommended that companies pay attention to the application of work discipline and work experience in order to improve employee performance. However, this application is not the only strategy that must be done, because there are many other strategies to improve employee performance which are not the author's study.